Healthcare resource utilization and costs among patients with direct oral anticoagulant or warfarin-related major bleeding. Issue 182 (October 2019) - Xu, Yan; Schulman, Sam; Dowlatshahi, Dar; Holbrook, Anne M.; Simpson, Christopher S.; Shepherd, Lois E.; Wells, Philip S.; Giulivi, Antonio; Gomes, Tara; Mamdani, Muhammad; Frymire, Eliot; Khan, Shahriar; et al.
Abstract: Introduction: Direct oral anticoagulants (DOACs) have expanded the options for antithrombotic therapy. DOAC-related major bleeds are associated with favorable outcomes compared to warfarin in clinical trials and routine practice. However, it is unclear whether management of DOAC-associated major bleeding incurs higher resource utilization and costs. Materials and methods: We screened medical records of patients ≥ 66 years with atrial fibrillation admitted to one of five tertiary care hospitals in Ontario, Canada with a hemorrhage. We abstracted bleeds involving DOACs or warfarin and linked them to administrative databases to capture length of hospital stay, blood product use, procedural interventions, intensive care unit (ICU) utilization and related direct medical costs. To control for confounders, multivariate logistic and linear regressions were used for binary and linear outcomes respectively. Results: Among 19, 061 records screened, 1978 (10.4%) cases involving 1632 patients met criteria of oral anticoagulant-associated bleeding. Baseline characteristics between DOAC and warfarin groups were similar. Blood product costs were higher for DOACs (all comparisons DOACs vs. warfarin, $1456 vs. $1109, mean difference $347, 95% CI $185 to $509), but length of stay and ICU use were similar. Mean direct medical costs did not differ ($9217 vs. $10, 790, adjusted relative ratio 0.94, 95% CI 0.84–1.05). Conclusions: Prior to introduction of DOAC-specific reversal agents, resource utilization and medical costs were comparable between DOAC- and warfarin-associated major bleeds, despite marginally higher blood product costs incurred by the former. Resource intensity associated with anticoagulant-related bleeding remains high, and our data provide measures for cost-effectiveness evaluation of emerging DOAC antidotes. Highlights: Costs of managing bleeds from direct oral anticoagulants (DOACs) are unknown. We compared resource use and costs of 1978 major bleeds from DOACs and warfarin. Blood product costs were higher for DOAC-associated bleeds compared to warfarin. However, DOAC bleeds did not incur higher total costs compared to warfarin. Major bleeds from dabigatran and factor Xa inhibitors had similar treatment costs.